Othello, April - Unknown (Tufts Archival Research Center, 2014)
8 x 6 in., photographic print. Photograph showing Joe Nye, Alfredo Cary, Muriel Simonson, Doc Andrews, Ralph Hanso, Phil Bridges, Chet Gilson and Carol Coburn performing in 'Othello,' a play produced at Tufts in April, 1928.